Klausa Relatif dalam Bahasa Indonesia dan Padanannya dalam Bahasa Mandarin - Xu Yunyu (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
This paper is about the compliments in conversational Mandarin. The use of praise many usesexpressions are lexical meaning can not be understood without looking at the situation behind thespeech of praise. Moreover, the meaning of praise in Mandarin conversation can not be seen only fromthe meaning of the word meaning per word shape. Thus, it can be concluded that the various forms ofexpression of praise in Mandarin can not be separated from the context of the speech. It is based on thetracking of lexical meanings of words that became an element in the expression of praise.